The masterpiece - Rivers, Francine, 1947- (Tyndale House Publishers, Inc., 2018)
Struggling to make a home for herself and her five-month old son Samuel, Grace Moore accepts a position as a personal assistant to Roman Velasco, a temperamental successful artist.